FRI0457 Uveitis incidence in patients with inflammatory lumbar pain. (23rd January 2014) - Cojocaru-Gofita, I.-R.; Cojocaru, I.; Vreju, F.; Musetescu, A.; Ciurea, R.; Barbulescu, A.; Florea, M.; Rosu, A.; Ciurea, P.
Abstract : Background: Spondyloarthritis (SpA) defines a group of interrelated diseases with heterogeneous clinical presentation. Regarding the shared distinguishing features one can mention uveitis as an important extraarticular involvement with a highly suggestive impact on the future evolution of SpA. Objectives: To investigate the prevalence of uveitis in patients with recent onset of inflammatory lumbar pain (ILP) which can be suggestive for developing SpA and to assess the interrelation of uveitis with other specific features of SpA patients. Methods: We enrolled 49 patients with a reported onset of ILP within a maximum of 3 months prior to the referral. All patients were assessed in the Rheumatology Department over a 3 year period, between 2009-2012. The subjects were included based on their personal evolution into different disease group, they had a mean age of 46.3±5 years aut of which 36 males and 13 females. Patients were monitored and reevaluated every 3 months during the first year and then every 6 months for the final 2. Positive diagnosis of SpA was based on the established criteria such as: the New York modified criteria for ankylosing spondylitis (AS). Uveitis was defined by an ophthalmologic episode diagnosed as such by an ophthalmologist. Data on the baseline functional status, imaging features, and serologic tests were compared in patients with and without uveitis. Factors associated with the presence of uveitis were identified both through univariate and multivariate statistical analysis (logistic regression) Results: The prevalence of uveitis at inclusion was 10.2 %. Uveitis was observed after the first episodes of ILP in 40 % of patients. The presence of uveitis was significantly associated (univariate) with pain in the lumbar spine, infection preceding inflammatory disease, a previous positive diagnosis of inflammatory bowel disease (IBD); enthesitis or radiologic evident coxo-femural joint involvement, but we could not certify a relation with the fulfillment of specific classification criteria, HLA-B27, Bath Ankylosing Spondylitis Disease Activity Index or the Bath Ankylosing Spondylitis Functional Index. Stastical multivariate analysis showed a positive association between uveitis and pain in the lumbar spine, infection preceding inflammatory disease, a previous diagnosis of IBD (P < 0.05). Conclusions: Our study showed association of ILP with the onset of IBD and infectious episodes which suggests an important role of environmental factors in the incidence of uveitis in SpA. These data stand the ground for a more thorough approach of the patient whom presents with an uveitis episode since they might already be eligible for the inclusion in a SpA category and evaluated accordingly. Disclosure of Interest: None Declared